2017
DOI: 10.3892/or.2017.5433
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of bladder cancer molecular mechanisms based on miRNA-mRNA regulatory network

Abstract: To explore the complex molecular mechanisms of bladder cancer, mRNA and miRNA expression profiles were combined for systematic analyses. A total of 18 common differentially expressed genes (DEGs) were identified from two mRNA expression datasets which consisted of 206 tumor and 74 normal tissues. Then, survival analysis based on the SurvExpress database showed that the common DEGs were able to significantly differentiate low- and high-risk groups in 4 public bladder cancer datasets (p<0.01). Notably, the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
1
5
0
1
Order By: Relevance
“…Similarly studies show that FLNC with low expression in BC was involved in tumor migration and invasion (55). In addition, this study showed that FLNC is lowly expression in BC.…”
Section: Discussionsupporting
confidence: 71%
“…Similarly studies show that FLNC with low expression in BC was involved in tumor migration and invasion (55). In addition, this study showed that FLNC is lowly expression in BC.…”
Section: Discussionsupporting
confidence: 71%
“…Our group has demonstrated that metastatic OS cells have higher levels of ALDH expression and activity, correlating with a metastatic phenotype in vitro [ 10 ]. Cancer cells with high ALDH have demonstrated enhanced tumorigenicity across multiple subtypes, including lung [ 21 ], breast [ 22 ], ovarian [ 23 ], prostate [ 24 ], bladder [ 25 ], esophageal [ 26 ], melanoma [ 27 ], and leukemia [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the relationship between urinary tumors and miR-145, miR-205 indicate that a large number of miRNAs have been involved in tumor progression (Catto et al, 2011;Simonato et al, 2013;Braicu et al, 2015;Chen et al, 2017). Some people also analyzed the differentially expressed miRNAs and their target genes in BC from the perspective of the network, and it is pointed out that miRNAs participate in the occurrence and development of BC by regulating their target genes, and are related to BC recurrence (Guancial et al, 2014;Jin et al, 2015;Li et al, 2017;Zhao et al, 2017). LncRNAs and mRNAs can form complex coexpression networks in various diseases including BC, and promote the development of BC by regulating proteincoding genes (Cao et al, 2018b;Li et al, 2018;Chen et al, 2019a;Chen et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%